Seasonal Patterns of Foreign Tourist Visits to Samosir (International Journal of Architecture and Urbanism, 2022)
The seasonal pattern of tourist visits is an important factor to consider when developing tourism marketing policies. This study attempts to determine seasonal trends of visitor visits to Samosir over the last three years using the seasonality ratio, Gini coefficients, and seasonality index as calculating methods.. This research shows several things. initial, tourist visits to Samosir show an insignificant level of variation, and similar patterns of seasonal variation are found in 2018, 2019, and 2020. Second, tourist visits to Samosir have a relatively even distribution per month with low seasonality or the difference between tourist visits. foreign countries per month have a negligible difference in worth Third, the peak season for tourist visits to Simanindo occurs in January, June, and December, with a significant increase over the preceding month, and the decline slows as the off-peak season approaches. As a result, specific resource allocation and marketing tactics are required to optimize each seasonal phase